MEDICAL AND SURGICAL APPROACH FOR CHERRY EYE IN AN AMERICAN BULLY DOG - Dinda Meilinda Br Sitepu; Anak Agung Gde Jayawardhita; I Nengah Wandia (Buletin Veteriner Udayana, 2025)
Cherry eye is a condition characterized by the prolapse of the nictitating gland due to weak connective tissue attachment, resulting in a visible red mass resembling a cherry. A 5-month-old female American Bully Ecotis dog, weighing 8.7 kg, presented with a protruding mass in the left eye, which had been observed for one month prior to surgery. Hematological examination revealed lymphocytosis, thrombocytosis, and low Platelet Distribution Width (PDW), suggesting mild inflammation. The diagnosis of cherry eye was confirmed through physical and clinical examinations, with a fausta (favorable) prognosis. Surgical correction was performed using the Morgan Pocket Technique to reposition the gland. Postoperative care included intramuscular cefotaxime (1.74 mL) and meloxicam (0.3 mL), followed by oral meloxicam (0.116 mg/day for 3 days) and topical gentamicin sulfate ointment (0.3%, applied TID for 7 days) to prevent infection. The surgical site showed complete healing by day 14, with no recurrence observed. This case highlights the effectiveness of the Morgan Pocket Technique combined with adjunctive medical therapy in managing cherry eye in dogs.